Pengaruh Word of Mouth, Promosi Melalui Medsos dan Kualitas Pelayanan terhadap Keputusan Konsumen dalam Memilih Wedding Organizer Ainasalsabila_Mua Kecamatan Pungging Kabupaten Mojokerto - Shokhifah, Nur Rahmawati Vivi; Lukito, Harjo; Muzrifah, Risa Amalia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The public's response to the field of mua services is increasingly developing, so this research aims to analyze and determine the influence of word of mouth variables, promotion through social media and service quality, which have a significant partial and simultaneous effect on consumer decisions in choosing the Ainasalsabila_mua wedding organizer, Pungging District, Mojokerto Regency. The data collection technique was carried out by distributing questionnaires. Research data sources utilize primary and secondary data. The research method is a quantitative method with the total sample determined using a purposive sampling technique using the Slovin formula of 110 respondents from a population of 150. Based on the test results with SPSS version 26, the results obtained are Y = 0.669 + 0.471X1 + 0.263X2 +0.104X3. Simultaneously using the F test, it proves that the variables word of mouth (X1), promotion via social media (X2) and service quality (X3) have an influence on consumer decisions (Y) significance 0.000. The t test proves that the word of mouth variable (X1) partially has a significant effect on the consumer decision variable with a significance of 0.000. The promotion variable via social media (X2) partially has a significant effect on the consumer decision variable with a significance of 0.000. The service quality variable (X3) partially has a significant influence on the consumer decision variable with a significance of 0.002. The dominant influence using a comparison of beta values proves that the word of mouth variable (X1) is the dominant independent variable influencing the dependent variable, namely consumer decisions, with a beta value of 0.471.